2014
DOI: 10.3390/ijerph111011015
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oral Health Behaviors on Dental Caries in Children with Intellectual Disabilities in Guangzhou, China

Abstract: Dental care is consistently reported as one of the primary medical needs of children with disabilities (IDC). The aim of the present study was to explore the influence of oral health behaviors on the caries experience in children with intellectual disabilities in Guangzhou, China. A cross-sectional study was carried out in 477 intellectually disabled children, 12 to 17 years old, who were randomly selected from special educational schools in Guangzhou. A self-administered parental questionnaire was used to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
48
1
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(75 citation statements)
references
References 33 publications
6
48
1
8
Order By: Relevance
“…Compared to other populations with disabilities, Liu et al and Pradhan et al found that 76.4% and 73% of the respondents, respectively, had not visited the dentist in the last year, similar to estimates for other disadvantaged groups, such as the homeless, but considerably higher than those of our study, possibly due to differences in sample composition. Pan et al also observed that 78% of the individuals with disability did not undergo regular appointments every 6 months, like our sample, in which 71.6% of the individuals had not visited the dentist in the last 6 months.…”
Section: Discussionsupporting
confidence: 79%
“…Compared to other populations with disabilities, Liu et al and Pradhan et al found that 76.4% and 73% of the respondents, respectively, had not visited the dentist in the last year, similar to estimates for other disadvantaged groups, such as the homeless, but considerably higher than those of our study, possibly due to differences in sample composition. Pan et al also observed that 78% of the individuals with disability did not undergo regular appointments every 6 months, like our sample, in which 71.6% of the individuals had not visited the dentist in the last 6 months.…”
Section: Discussionsupporting
confidence: 79%
“…In individuals with rare genetic disorders associated to physical and/or motor disability such as CdCS patients, the oral mucosa care is usually inadequate [10,11], and furthermore in those low-income patients [12]. In our patient, we could confirm an adequate oral care on behalf of the patient´s family and dentists.…”
Section: Discussionsupporting
confidence: 57%
“…Schoolchildren with ILD may not be able to express pain associated with dental caries due to their inadequate ability to describe pain to their parents and/or dentists. Hence, they might require more advanced attention and management of their dental treatment, including oral health promotion programmes for their parents and regular dental visits to improve their oral health …”
Section: Discussionmentioning
confidence: 99%